2021
DOI: 10.1016/j.ymgmr.2021.100726
|View full text |Cite
|
Sign up to set email alerts
|

Congenital disorders of glycosylation: Prevalence, incidence and mutational spectrum in the Polish population

Abstract: Introduction The incidence and prevalence of congenital disorders of glycosylation (CDG) have not been well established. The aim of the study was to evaluate the prevalence, incidence and genotypes of CDG patients diagnosed during the last 23 years in Poland (1997 – 30th October 2020). Material and methods The diagnosis was based on serum Tf IEF which is performed at The Children's Memorial Health Institute (CMHI) in Warsaw. Based on demographic data, the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…If we exclude FUK-CDG and MAN2B2-CDG, the prevalence in Europeans is slightly lower, one in 24,000. Compared to available data ( Vals et al, 2018 ; Lipinski et al, 2021 ), the expected and observed prevalence differ. The lower observed prevalence might be somewhat underestimated because of undiagnosed patients due to different causes such as unrecognized phenotypes, negative screening results or limited access to different metabolic and molecular studies.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…If we exclude FUK-CDG and MAN2B2-CDG, the prevalence in Europeans is slightly lower, one in 24,000. Compared to available data ( Vals et al, 2018 ; Lipinski et al, 2021 ), the expected and observed prevalence differ. The lower observed prevalence might be somewhat underestimated because of undiagnosed patients due to different causes such as unrecognized phenotypes, negative screening results or limited access to different metabolic and molecular studies.…”
Section: Discussioncontrasting
confidence: 69%
“…Mainly at the expense of PMM2-CDG, type 1 defects are more frequently diagnosed than type 2 defects ( Peanne et al, 2017 ; Medrano et al, 2019 ) but compared to PMM2-CDG, other defects occur much seldom. The estimated combined prevalence of CDG among the Saudi population is 14 per million ( Alsubhi et al, 2017 ), whereas, in Poland, the prevalence is approximately one case per million ( Lipinski et al, 2021 ). The worldwide individual prevalence of different defects remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…After the diagnosis of CDG-I based on serum Tf IEF, phosphomannomutase-2 (PMM2) and phosphomannose isomerase (PMI) activity should be measured in fibroblasts or leukocytes in the proper clinical context (1)(2)(3)(4)85). PMM2-CDG has the best-defined clinical phenotype and is by far the most frequent N-glycan assembly defect (99). PMI activity should be measured in case of clinical and biochemical presentation mainly expressed by the liver.…”
Section: Diagnostic Processmentioning
confidence: 99%
“…Serum Tf isoforms were analyzed by isoelectrofocusing (IEF) agarose gel electrophoresis according to the modification introduced in our laboratory (Adamowicz et al, 1996;Adamowicz et al, 2007) of the method described by Van Eijk and others (Van Eijk et al, 1982). Since 1995, the CDG selective screening based on serum Tf IEF has been performed at our Institute (CMHI) for patients from the entire country (Bogdańska et al, 2021;Lipiński et al, 2021). During the years of 1995-2020, a total number of 23,183 serum Tf isoform analyses from pediatric patients have been performed.…”
Section: Serum Transferrin (Tf) Isoforms Isoelectrofocusingmentioning
confidence: 99%